2022
DOI: 10.1002/14651858.cd015308
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 blocking agents for treating COVID-19

Abstract: Interleukin-1 blocking agents for treating COVID-19 (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 46 publications
5
35
0
2
Order By: Relevance
“…In contrast, blocking of IL-1 signaling with anakinra had no substantial effect on reducing mortality of critically ill COVID-19 patients. 88 , 89 However, there have been reports that long-term metformin users have a strikingly reduced risk of fatal courses, 90 , 91 with one study showing that this is especially true for women with obesity or type 2 diabetes. 92 It was recently shown that metformin blocks NLRP3 inflammasome activation including inhibition of IL-1β and IL-6 in alveolar macrophages attenuating SARS-CoV-2-induced ARDS in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, blocking of IL-1 signaling with anakinra had no substantial effect on reducing mortality of critically ill COVID-19 patients. 88 , 89 However, there have been reports that long-term metformin users have a strikingly reduced risk of fatal courses, 90 , 91 with one study showing that this is especially true for women with obesity or type 2 diabetes. 92 It was recently shown that metformin blocks NLRP3 inflammasome activation including inhibition of IL-1β and IL-6 in alveolar macrophages attenuating SARS-CoV-2-induced ARDS in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“… 16–21 , 23–44 , 46–51 , 53–57 , 59–69 , 73–79 The impact factor published in SCI journals ranged from 1.04 to 39.89, with an average of 11.72 and a standard deviation of 11.30. The impact factor of 64.1% studies was >5, 16–20 , 23 , 26 , 27 , 30 , 32 , 33 , 36 , 37 , 39–44 , 46 , 47 , 49–51 , 54–57 , 60–64 , 67–69 , 73–76 , 79 the impact factor of 17.2% studies was >15. 16 , 17 , 23 , 42 , 43 , 51 , 62–64 , 74 , 76 LSRs were published in journals with high impact factor, which indicated COVID-19 related studies have attracted much attention from readers ( Table 1 ).…”
Section: Resultsmentioning
confidence: 96%
“…Possibly, the clinical severity of these patients was milder compared with the ones in the COV-AID trial. A recent systematic review of RCTs targeting IL-1 signaling in COVID-19 patients could not find evidence for an important beneficial effect of IL-1 blocking agents [115] .…”
Section: Discussionmentioning
confidence: 99%